(untitled) (ENTHYMEMA, 2020)
This paper aims to discuss the phenomenon of Lolita’s hypertexts in the light of the issues of trauma and the unspeakable, adopting the framework offered by psychiatry and psychoanalysis on pedophilia. In the first chapter I will be particularly concerned with three revisionary texts, namely Kim Morrissey’s Poems for Men Who Dream of Lolita, Christophe Tison’s Le Journal de Lolita and Emily Prager’s Roger Fishbite, whereas the second one will provide a close analysis of another revisionary text, Diario di Lo, written by Pia Pera.